Physiological indicators for pain - Bento, Ana Luísa Baltazar (2021)
Pain is a complex, biopsychosocial phenomenon that arises from the interaction of multiple neuroanatomic and neurochemical systems with several cognitive and affective processes. Nowadays, the assessment of pain intensity still relies, mainly, on the use of self-reporting scales. These instruments rely on the individual to process external information and communicate a response, which may not always be a reliable method. The autonomic nervous system (ANS), which is divided into the parasympathetic nervous system (PNS) and the sympathetic nervous system (SNS), is a part of the human nervous system. The ANS functions as the subconscious regulator of the body. Studies have shown a connection between the perception of pain and exacerbated stress response on the ANS. As a result, there has been an increase in research on the use of autonomic reactivity, usually through physiological indicators, as an objective marker for pain. In this study four different physiological signals (electrocardiogram – ECG; two electromyogram – EMG, electrodermal activity – EDA and blood pressure – BP) were, simultaneously, recorded to study their relation to pain. For that, a pain-inducing protocol, more specifically Cold Pressor Task (CPT), which requires the participant to place their hand into cold water, was used. The data was processed and the differences between the painful and non-painful periods were investigated. The use of a higher number of physiological signals is a step forward in the studies of this kind, since it may allow a more solid analysis of the effects of pain that occur, concurrently, on the body. Consequently, this, also, enables a better validation of the hypothesis of these studies, by putting in juxtaposition the conclusions from the various systems. The results, for the ECG and BP, showed a statistically significant increase in the heart rate and blood pressure, during the painful periods, in comparison, with non-painful periods. Additionally, heart rate variability features demonstrated a decrease in the PNS influence. From the EMG, which was recorded on the trapezius and triceps muscle, the time-domain feature results showed an increase in power and contraction force of the muscle during the CPT. However, frequency-domain features did not display meaningful information regarding the reaction of the musculoskeletal system to the painful stimulus. Overall, the trapezius was able to provide more helpful information regarding the behaviour of the body. Lastly, the EDA, also showed an adjustment of the sudomotor activity, implying an increase in the SNS activity in the body during the CPT. These results indicate that in general, the features point to an autonomic reaction of the body in response to pain, mainly a decrease in the PNS activity, accompanied by an increase in the reactivity of the SNS.